2015
DOI: 10.4103/1305-7456.156834
|View full text |Cite
|
Sign up to set email alerts
|

Root canal retreatment using reciprocating and continuous rotary nickel-titanium instruments

Abstract: Objective:The complete filling material removal during endodontic retreatment is a clinical procedure difficult to achieve. The aim of this study was to evaluate the efficacy of reciprocating and continuous rotary nickel-titanium instruments used in root canal retreatment.Materials and Methods:Forty freshly extracted human premolars were cleaned and shaped by the crown-down technique, followed by filling by the lateral compaction technique. The teeth were randomly separated into two groups (n = 20), according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 17 publications
5
33
1
2
Order By: Relevance
“…The manufacturer of Reciproc instruments claimed that also retreatment cases can be safely solved with these instruments as long as the manufacturer's instructions are followed (Yared 2013b). In several in-vitro studies this claim was confirmed (de Souza et al 2015;Marfisi et al 2015;Zuolo et al 2013). But only completely filled root canals were retreated in these studies.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…The manufacturer of Reciproc instruments claimed that also retreatment cases can be safely solved with these instruments as long as the manufacturer's instructions are followed (Yared 2013b). In several in-vitro studies this claim was confirmed (de Souza et al 2015;Marfisi et al 2015;Zuolo et al 2013). But only completely filled root canals were retreated in these studies.…”
Section: Introductionmentioning
confidence: 65%
“…Moreover this publication contains no information about the frequency of Reciproc to reach full WL. There are only invitro studies that evaluate the general possibility to use Reciproc instruments for endodontic retreatments (de Souza et al 2015;Marfisi et al 2015;Zuolo et al 2013). All publications come to the conclusion, that Reciproc was the fastest system for retreatment.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%
“…The method used for the quantification of the filling material remaining in the root canal after the endodontic retreatment was the radiographic image [5,22]. It is the most used method by the clinicians and easily accessable for the dental surgeons; the radiographic analysis, on the other hand, only produces one two-dimensional image of the sample [2,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…When a treatment failure is observed during clinical / radiographic control, the following procedures are: Root canal retreatment or apical surgery, which can be successful when correctly indicated. However, whenever access to the root canal is possible, the endodontic retreatment must be the first choice [2].…”
Section: Introductionmentioning
confidence: 99%
“…The other is the invention of reciprocating files for cleaning and shaping. [1617] Numerous studies have proved that reciprocation motion increases the cyclic fatigue resistance of files. [181920]…”
Section: Introductionmentioning
confidence: 99%